Avitellina centripunctata infection in Nilgai (Boselaphustragocamelus) (International Journal of Scientific Research and Management (IJSRM), 2017)
Nilgai(Boselaphustragocamelus) are native to India and Pakistan, where they are the largest species of antelope. It is one of the most commonly seen wild animals of central and northern India, often seen in farmland or scrub forest. The main threat to this species is the loss of their habitat due to human population growthand encroachment of forest also they are acting as carrier for many infectious agents including parasites. Adult tapeworm parasites in herbivores animals’majoratily belong to family Anoplocephalidae. Their infestations in animals adversely affect the growth, production and immune status of animals (Narsapur, 1988). Their systemic study in wild as well as domesticated animals is of upmost importance. Information regarding the prevalence of tape worm infestation in Nilgai from central India is lacking. The present communication is dealing with the occurrence of tapeworm infestation in Nilgai from central India.